Optimalisasi Kajian Hukum Sosial Terhadap Kejahatan Seksual pada Remaja - Syarinia Febriantika Agung; Zahwa Aliya (Terekam Jejak Publisher, 2024)
This research examines the factors that influence the frequent occurrence of violence against children and how to overcome the negative impacts experienced by victims. Criminology is closely related to the sciences that study the conception of criminal cases related to crime, which is associated law and violations of norms. The cause of violence viewed criminologically is due to the increasing number of influences that contaminate the psychology of the perpetrator. This is caused by economic problems and environmental culture which is slightly distorted in the process of raising children. The consequences of violence can be overcome through rehabilitation and psychological support for victims. Criminology studies are needed to evaluate various aspects outside the law, especially social legal study. This research is empirical descriptive legal research and used qualitative method.